Managerial Accompaniment And Financial Management For Business Sustainability In Dinoyo Ceramic Village - Anthon Efani; Asfi Manzilati; Suprayogi Suprayogi; Mariyana Sari (Sekolah Pascasarjana Universitas Brawijaya, 2022)
Dinoyo Village is a ceramic craft center in Malang City. The cultural potential of the Dinoyo community, especially ceramic craftsmen, which has survived to this day is one of the basics in the effort to preserve the culture itself. The objectives of the service activities of the Serving Doctoral Program include: (1) integrating the performance of Higher Education (University of Brawijaya), with Dinoyo Ceramic Village to improve the sustainability of Dinoyo Ceramic Village, (2) creating business sustainability, through business management training and financial management, (3) assistance in website development, (4) increasing the competitiveness of Dinoyo Ceramic Village products, through product branding and educational tourism branding, (5) utilizing potential water sources as supporting educational tourism, (6) strengthening the regional innovation system of Dinoyo Ceramic Village through rights services. copyright, (7) increasing the role of Brawijaya University in the development of the campus area by involving students. Through managerial assistance in this service program, it is hoped that Dinoyo Ceramic Village will be able to become a sustainable MSME business. Sustainability in question is not only the sustainability of productivity but also sustainability as a literacy and preservation center in Malang City which has legal protection for the products or works produced. In turn, the Ceramic Village can become a cultural and literacy icon in Malang City.